Lactobacillus as Anti-Biofilm Therapeutics: Formulation and Delivery Challenges in Clinical Translation - B.V.N.V, Bharathi; Pullagura, Anila Rani; Essgir, Prem Kumar; Bharathnaik, R.; Dokka, Muni Kumar (Journal of Neonatal Surgery, 2025)
Background: Biofilm-associated infections contribute to nearly 65% of all microbial infections and are notoriously resistant to conventional antibiotics. The protective extracellular polymeric matrix and metabolic heterogeneity of biofilms make treatment particularly challenging. Lactobacillus species have emerged as promising anti-biofilm agents due to their ability to produce antimicrobial compounds, disrupt biofilm architecture, and enhance host immune responses. However, their clinical application remains limited by significant formulation and delivery barriers. The objective of the review is to critically evaluate the anti-biofilm potential of Lactobacillus, identify the key challenges hindering its clinical translation, and explore technological and regulatory strategies to overcome these limitations. Methods: This review integrates current literature on the antimicrobial mechanisms of Lactobacillus, assesses the environmental and physiological stressors impacting therapeutic viability, and analyzes recent advances in protective formulation technologies, genetic engineering, and synergistic therapies. The review also examines the regulatory landscape governing Live Biotherapeutic Products (LBPs). Results: Lactobacillus exerts multi-modal anti-biofilm effects through the production of organic acids, bacteriocins, biosurfactants, and hydrogen peroxide, alongside competitive exclusion and immunomodulation. However, survival is severely compromised by manufacturing stress, gastric acidity, bile exposure, oxidative damage, and microbiota competition. Technological innovations such as microencapsulation, enteric coatings, biofilm-based delivery platforms, and CRISPR-based strain enhancements significantly improve viability and efficacy. Combination therapies with bacteriophages and matrix-degrading enzymes offer synergistic benefits. Nonetheless, the regulatory framework for LBPs demands extensive characterization, safety assurance, and novel clinical trial designs, presenting additional hurdles. Conclusion: Lactobacillus-based therapeutics offer a promising solution for biofilm-related infections, but successful clinical translation demands integrated advances in formulation, genetic engineering, regulation, and personalized strategies—driven by interdisciplinary collaboration